The Impact of Tax Planning and Tax Avoidance on Firm Value with The Moderating Role of Tax Havens - Safina Salwa Binti Sunarya; Nur Rahmanti Ratih; Dewi Wungkus Antasari (Dinasti Publisher, 2025)
This research examines the impact of tax planning and tax avoidance on firm value with the moderating role of tax havens. The method in this study uses quantitative. Research data comes from multinational companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023, with a population of all major sectors of companies listed on the IDX. The sample was determined using the purposive sampling method. This research uses quantitative methods with the main analysis including multiple regression to test the direct effect of independent variables on firm value, and Moderated Regression Analysis (MRA) to measure the moderating role of tax havens. The results of this study indicate that the relationship between tax planning has a positive effect on firm value, while tax planning and tax avoidance on firm value are not significant, either directly or with the moderation of tax havens.